Renal lymphoma: an unusual cause of extrahepatic biliary obstruction. Issue 852 (October 1996) - Abbas, Z.; Johnston, D. A.; Murray, F. E.
Abstract : This report describes a case of lymphoma arising in a kidney subjected to previous pyelolithotomy, lithotripsies and percutaneous nephrolithotomy. The tumour had invaded the pancreas and duodenum, resulting in extrahepatic biliary and gastric outlet obstructions. Fine-needle apiration cytology guided by computed tomography failed to suggest the diagnosis which was confirmed only on laparotomy and open biopsy. Drainage procedures were performed to relieve the obstructions. To our knowledge this is the first case report of renal lymphoma presenting with extrahepatic biliary obstruction.